Crystallization and preliminary X-ray analysis of the haloalkane dehalogenase DatA from Agrobacterium tumefaciens C58 - Mase, Tomoko (International Union of Crystallography, 2012)
Haloalkane dehalogenases are enzymes that catalyze the hydrolytic reaction of a wide variety of haloalkyl substrates to form the corresponding alcohol and hydrogen halide products. DatA from Agrobacterium tumefaciens C58 is a haloalkane dehalogenase that has a unique pair of halide-binding residues, asparagine (Asn43) and tyrosine (Tyr109), instead of the asparagine and tryptophan that are conserved in other members of the subfamily. DatA was expressed in Escherichia coli, purified and crystallized using the sitting-drop vapour-diffusion method with a reservoir solution consisting of 0.1 M CHES pH 8.6, 1.0 M potassium sodium tartrate, 0.2 M lithium sulfate, 0.01 M barium chloride. X-ray diffraction data were collected to 1.70 Å resolution. The space group of the crystal was determined as the primitive tetragonal space group P422, with unit-cell parameters a = b = 123.7, c = 88.1 Å. The crystal contained two molecules in the asymmetric unit.